Ammonia volatilization losses in Tanzania grass fertilized with urea - Soares Filho, Cecilio Viega [UNESP]; Cecato, Ulysses; Ribeiro, Ossival Lolato; Roma, Claudio Fabricio da Cruz; Beloni, Tatiane (FapUNIFESP (SciELO), 2015)
Gaseous losses are the main factors affecting the efficiency of nitrogenous fertilizers in pastures. To evaluate NH3-N volatilization losses in Tanzania grass fertilized with urea in autumn, spring and summer, a completely randomized design with repeated measurements over time and fifteen replicates was used. Plots were represented by urea levels (50; 100 and 150 kg ha-1 N) and subplots by time after fertilization (1; 2; 3; 6; 9; 12 and 15 days). The interaction between fertilization leveland time after urea application was significant for the accumulated NH3-N volatilization. Urea application leads to higher percentage N losses in the first three days after application. The average cumulative NH3- N loss for the three occasions (different seasons of the year) was 28%, 20% and 16% of N applied for fertilizer doses of 50; 100 and 150 kg ha-1 of N, respectively. The season of the year influenced NH3-N loss pattern and volume, with the lowest values recorded in spring, followed by summer and autumn. The cumulative NH3-N volatilization loss varies from 78 to 90% up to the third day after application of the total NNH3 loss.

As perdas gasosas são os principais fatores de ineficiência do uso de fertilizantes nitrogenados nas pastagens. Com o objetivo de estimar a perda N-NH3 por volatilização foi realizado um experimento com capim Tanzânia adubada com ureia nas estações de outono, primavera e verão. Adotou-se um delineamento experimental inteiramente casualizado, com medidas repetidas no tempo com quinze repetições. Nas parcelas, as doses de N-ureia (50, 100 e 150 kg ha-1 de N-ureia) e, nas subparcelas, o período depois da adubação nitrogenada (1, 2, 3, 6, 9, 12 e 15 dias). A interação entre o nível de adubação e o período depois da aplicação de ureia foi significativa para a variável volatilização acumulada de N-NH3. A aplicação da ureia acarreta perdas percentuais mais elevadas de N nos três primeiros dias após a aplicação. A perda média acumulada de N-NH3 no período para as três estações do ano representou 28%, 20% e 16% do N aplicado nas adubações com 50, 100 e 150 kg ha-1 de N-ureia, respectivamente. A estação do ano influenciou no padrão e na quantidade das perdas, com menores valores encontrados na primavera, seguidos do verão e outono. A perda acumulada de N-NH3 por volatilização variou de 78 a 90% até o terceiro dia após aplicação do total perdido.
Perdas de amônia por volatilização em capim-Tanzânia adubada com ureia
Keywords: Panicum maximum; Nitrogen fertilizer; Pasture; Panicum maximum; Fertilizante nitrogenado; Pastagem